Pediatric liver transplantation in Latin America: Where do we stand?. (3rd February 2016) - Feier, Flavia; Antunes, Eduardo; D′Agostino, Daniel; Varela‐Fascinetto, Gustavo; Jarufe, Nicolas; Patillo, Juan C.; Vera, Alonso; Carrasco, Felix; Kondo, Mario; Porta, Gilda; Chapchap, Paulo; Seda‐Neto, Joao
Abstract: LT started in LA in 1968, and pediatric LT records are available starting in the 1990s. Currently, eight countries perform pediatric LT in LA. Registries by national organizations fail to report robust data on pediatric LT. The aim of this paper was to report on the pediatric LT activity in LA. Data were gathered retrospectively through information available in the national registries websites and from local centers. Of the eight countries that report pediatric LT activity, Brazil, Argentina, Mexico, and Colombia have adequate registries of the numbers of LT performed. These countries concentrate most of the activity for pediatric LT. A total of 4593 pediatric LT were reported in LA. Websites for national organizations do not provide open data on post‐transplant survival rates or waiting list mortality. The information herein is based on reports by local centers. Overall, survival from select centers is similar to that reported on North American and European registries, between 80 and 90% in the first year post‐transplant. In conclusion, pediatric LT activity is growing in LA, especially in Brazil and Argentina. However, the lack of an appropriate LA registry restricts the assessment of quality and therefore restricts interventions aimed at quality improvements in different regions.